PERBANDINGAN KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR FISIKA SISWA ANTARA MODEL PEMBELAJARAN SIKLUS BELAJAR EMPIRIS INDUKTIF DENGAN PEMBELAJARAN MODIFIED FREE DISCOVERY-INQUIRY - Hanny Kruisdiarti; I Dewa Putu Nyeneng; Undang Rosidin (Jurnal Pembelajaran Fisika, 2013)
Learning process need an implementation of some learning inovation to help student reach their education’s goal. This research compared the critical thinking skills and the learning outcome of physics among the learning model of empirical inductive learning cycle with modified free discovery–inquiry. The purpose of this research to determine, (1) an average differences of critical thinking ability between the learning model of empirical-inductive learning cycle and modified free discovery-inquiry; (2) an average differences of learning outcome of physics between the learning model of empirical-inductive learning cycle and modified free discovery-inquiry. This research was conducted in the second semester of the academic year 2012/2013 at the SMP N 3 Bandarlampung. The population in this research were all students of class VIII. The sample is consisted of two classes which is taken by using cluster random sampling technique. The samples are VIIIC and VIIID. The analysis technique of Learning outcomes data was using N-gain scores, while critical thinking skills data was analyzed using percentage grades. Based on the results of the test, the average score of student’s critical thinking skills in the empirical inductive learning cycle class by 66.26% and the class of modified free-inquiry discovery by 75.35%. For learning outcomes, empirical inductive learning cycle class earned an average N-gain learning outcomes of 0.67 and the class of modified free-inquiry discovery earned 0.76. Thus, these results indicate that the average of critical thinking skills and learning outcome in the modified class free discovery-inquiry is higher than the class of empirical inductive learning cycle.Keywords : Critical Thinking Skills, Learning Outcome, Empirical InductiveLearning Cycle, and Modified Free Discovery Inquiry.